2016
DOI: 10.1007/s00401-016-1592-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutant desmin substantially perturbs mitochondrial morphology, function and maintenance in skeletal muscle tissue

Abstract: Secondary mitochondrial dysfunction is a feature in a wide variety of human protein aggregate diseases caused by mutations in different proteins, both in the central nervous system and in striated muscle. The functional relationship between the expression of a mutated protein and mitochondrial dysfunction is largely unknown. In particular, the mechanism how this dysfunction drives the disease process is still elusive. To address this issue for protein aggregate myopathies, we performed a comprehensive, multi-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 84 publications
6
76
1
1
Order By: Relevance
“…Ultrastructural analysis of postmortem muscles show characteristic myofibrillar disruption and aggregation of desmin filaments in the myocardium 38, 39. In addition, mitochondrial dysfunction occurs early and acts causally in a wide variety of human protein aggregate disease pathogenesis affecting the central nervous system40, 41 and striated muscle tissue 16, 42. Muscle biopsy specimens from human desminopathies and myofibrillar myopathies showed evidence of mitochondrial pathology 43, 44.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrastructural analysis of postmortem muscles show characteristic myofibrillar disruption and aggregation of desmin filaments in the myocardium 38, 39. In addition, mitochondrial dysfunction occurs early and acts causally in a wide variety of human protein aggregate disease pathogenesis affecting the central nervous system40, 41 and striated muscle tissue 16, 42. Muscle biopsy specimens from human desminopathies and myofibrillar myopathies showed evidence of mitochondrial pathology 43, 44.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have noted that both mitochondrial morphology and positioning are altered in the muscles of DRCs 10, 16. It is unknown whether these alterations result in maladaptive changes in mitochondrial dynamics and directly contribute to mitochondrial dysfunction, resulting in cardiomyopathies in DRC.…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown that point mutations in genes of the subunits of an OxPhos complex affect the stability of another complex. Thus, complex III and complex IV are necessary for the assembly or stability of complex I [34, 35]. Moreover, it appears that supercomplexes are further organized into larger string structures.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial electron density and cristae morphology appear to be maintained in knockout muscle. Another cytoskeletal protein, the intermediate filament desmin is known to be important for proper mitochondrial morphology [28,29]. However the observed mitochondrial phenotype in Actg1-msKO and Actb-msKO is likely not impacted by changes in desmin, which was expressed at similar levels (Figure 3 A–B) and localization (Figure 3 C–E) relative to control muscle.…”
Section: Resultsmentioning
confidence: 94%